PENCEGAHAN KORUPSI PADA PENGELOLAAN KEUANGAN DESA (Studi Kasus: Desa Deme Dua dan Bubalango, Kecamatan Sumalata Timur, Kabupaten Gorontalo Utara) - Kadir, Yusrianto (Insan Cita : Jurnal Pengabdian Kepada Masyarakat, 2025)
Village financial management is a crucial aspect in the implementation of village autonomy that requires strict supervision to prevent corrupt practices. This community service activity aims to increase the understanding and awareness of village officials and the community about corruption prevention in village financial management. The service was carried out in Deme Dua and Bubalango Villages, East Sumalata District, North Gorontalo Regency on January 25, 2025. The method used was community education through socialization and interactive discussions. The results showed an increase in participants' understanding of the legal and practical aspects of corruption prevention in village financial management, including the application of the principles of transparency, accountability, and community participation. This activity contributes to strengthening village governance that is clean and free from corruption. Keywords : corruption prevention, village finance, governance, transparency, accountability